An exploratory study of white blood cell proportions across preeclamptic and normotensive pregnancy by self-identified race in individuals with overweight or obesity. (2nd October 2021) - Ray, Mitali; Heinsberg, Lacey W.; Conley, Yvette P.; Roberts, James M.; Jeyabalan, Arun; Hubel, Carl A.; Weeks, Daniel E.; Schmella, Mandy J.
ABSTRACT: Objective: Examine white blood cell (WBC) proportions across preeclamptic (n = 28 cases) and normotensive (n = 28 controls) pregnancy in individuals with overweight/obesity. Methods: WBC proportions were inferred from genome-wide DNA methylation data and compared by case/control status and self-identified race. Results: In Trimester 1, ean B cell proportions were suggestively lower in cases in the overall sample and significantly lower in White participants but not in Black participants. More significant WBC proportion changes were observed across normotensive than preeclamptic pregnancy. Conclusions: These findings in a small sample demonstrate need for additional studies investigating the relationship between self-identified race and WBCs in pregnancy.